1990
DOI: 10.1063/1.458909
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics studies of polar/nonpolar fluid mixtures. I. Mixtures of Lennard-Jones and Stockmayer fluids

Abstract: The results of canonical ensemble molecular dynamics calculations of mixtures of Lennard–Jones and Stockmayer fluids are reported. To study solely the influence of the polarity, the Lennard-Jones parameters were identical for both components. The excess mixing properties show a strong asymmetry with respect to composition for large dipolar strength. The free energy of mixing is obtained through a thermodynamic integration procedure. The results strongly suggest that, for reduced dipolar strengths μ2>3.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…[14][15][16][17][18] Third, the SM/LJ binary fluids can be used to study mixtures of polar and nonpolar fluids. [19][20][21] Fourth, SM clusters can be used to study the effect of dipole strength on structures of polar clusters. 9,22,23 As for the thermodynamic properties of the SM fluids, such as phase equilibria and surface tensions, a) Electronic mail: xzeng1@unl.edu most previous studies have been focused on the liquid-vapor equilibria [24][25][26][27][28][29] while few studies have reported the freezing points.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17][18] Third, the SM/LJ binary fluids can be used to study mixtures of polar and nonpolar fluids. [19][20][21] Fourth, SM clusters can be used to study the effect of dipole strength on structures of polar clusters. 9,22,23 As for the thermodynamic properties of the SM fluids, such as phase equilibria and surface tensions, a) Electronic mail: xzeng1@unl.edu most previous studies have been focused on the liquid-vapor equilibria [24][25][26][27][28][29] while few studies have reported the freezing points.…”
Section: Introductionmentioning
confidence: 99%
“…Adachi and Nakanashi 5,6 studied the self-association of methanol in benzene. De Leeuw et al [7][8][9][10] carried out an extensive series of simulations on Stockmayer and Lennard-Jones molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning simulation results, De Leeuw et al 23 studied the phase behavior of mixtures of Stockmayer and LennardJones molecules using molecular dynamics. They found that at high densities a demixing transition takes place.…”
Section: Introductionmentioning
confidence: 99%